Pleasure Domes and Sunbeams: An Anti-Oedipal Reading of “Kubla Khan” - Robert Tindol (Anglica. An International Journal of English Studies)
Samuel Taylor Coleridge’s 1797 poem “Kubla Khan” begins with the statement that Kubla Khan once caused a pleasure-dome to come into existence by dint of a kingly decree. The last line states that the narrator, should he gain suffi cient poetic vision, would have “drunk the milk of paradise” and would “build that dome in air.” A new reading may be derived from a focus on precisely what these lines say and what they imply within the perspective of Gilles Deleuze and Felix Guattari’s work Anti-Oedipus. If the process of the narrator’s gaining poetic insight is set in motion by a conscious decree from Kubla Khan, then an Anti-Oedipal reading considers whether the end result is simply the consequence a powerful individual’s wishes, or else is paradoxically a liberation from those wishes.